Conversion of nursing evidence to practice science: Translational nursing Hemşirelik kanıtlarının uygulamaya dönüştüğü bilim: Translasyonel hemşirelik - Şendir, Merdiye; Yaman, Rabia; Kızıl, Hamiyet; Özdemir, Cevriye; Kubat Bakır, Gizem (Journal of Human Sciences, 2019)
Today, enhancing the quality of healthcare, offering cost-effective healthcare, the increase in healthcare costs, knowledge management, healthcare preferences of the changing community, cost, effective healthcare policies and similar reasons have made it necessary to integrate evidence-based research findings into clinical practice. Evidence-based nursing practices are important to improve the quality and outcomes of nursing care and to make a difference in clinical practice. Translational nursing is a dynamic process defined as the initiation of research in the clinic where the research is carried out in order to fulfill this necessity. This process takes place through an intensive and complex interaction between researchers and the users of information and facilitates bridging the gap between scientific knowledge and its clinical use. When the examples of Translational Nursing from around the world are examined,"Translational Nursing" practices have been realized for a long time. Studies carried out in Turkey show that there are translational practices in nursing but this term is not used. It was aimed to emphasize, with this review, the importance of the use of the concept of “Translational Nursing” as a common terminology to integrate scientific knowledge with clinical practices. Extended English summary is in the end of Full Text PDF (TURKISH) file. Özet Günümüzde sağlık bakım kalitesinin arttırılması, maliyet-etkili bakımın verilmesi, sağlık bakımı maliyetlerindeki artış, bilginin yönetimi, değişen toplumun sağlık bakım tercihleri, maliyet, etkili bakım politikaları gibi nedenler kanıt düzeyi yüksek araştırma bulgularının klinik uygulamalar ile bütünleştirilmesini zorunlu hale getirmiştir. Hemşirelik uygulamalarının kanıta dayalı olması ise bakım kalitesini ve sonuçlarını iyileştirmek, klinik uygulamalarda fark yaratmak için önem taşımaktadır. Translasyonel hemşirelik; araştırmanın gerçekleştiği klinikte uygulanmaya başlanması olarak tanımlanan dinamik bir süreçtir. Bu süreç, araştırmacılar ve bilgiyi kullananlar arasında yoğun ve karmaşık bir etkileşim içinde gerçekleşerek bilimsel bilgi ve onun klinik kullanımı arasındaki boşluğu kaldırmaya yardımcı olmaktadır. Dünya literatürü incelendiğinde “Translasyonel Hemşirelik” uygulamalarının uzun zamandır gerçekleştiği görülmektedir. Ülkemizde yapılan çalışmalar incelendiğinde ise , hemşirelikte translasyonel uygulamaların olduğu ancak bu terimin kullanılmadığı belirlenmiştir. Bu derleme ile “Translasyonel Hemşirelik” kavramının bilimsel bilgi ile klinik uygulamaların bütünleştirilmesinde ortak terminoloji olarak kullanılması ve translasyonel bilimin uygulanmasının önemini vurgulamak amaçlanmıştır.